Barriers in Writing and Publishing Scientific Articles (Homoeopathy for All, 2021)
Scientific journals are the most important media for dissemination of scientific information. Writing and publishing research articles in high quality journals are important activities in a career of every scientist. But there are various barriers/ obstacles while writing and publishing the work especially for the novice writers. The literatures of published papers were reviewed to find various barriers/obstacles in writing and publishing scientific articles. The literatures were searched using the search engines Pubmed and Google scholar with the help of following keywords and their combinations: barriers, obstacles, writing, publishing, scientific article in the searching areas of title, keywords, abstract, and full text. More than 100 articles and reports were collected and twenty five of them were selected based on their relevancy. Various barriers to writing and publishing like lack of time, funding, writing skills, personal barriers etc., have been identified. Removing these obstacles/ barriers will facilitate in good writing and publication of research articles in scientific journals.
Keywords: Obstacle; barriers; challenges; writing